2011
DOI: 10.2320/matertrans.mc201004
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Magnesium Alloy AZ31 Processed by Compound Channel Extrusion

Abstract: We report microstructure evolution and mechanical properties of Mg alloy AZ31 processed by a new severe plastic deformation technique which combines forward extrusion, equal channel angular extrusion (ECAE) and change channel angular extrusion (CCAE). Under all of the processing temperatures ranging from 623 K to 723 K, the grain size of the as-extruded sample was remarkably refined, which is attributed to the grain subdivision and dynamic recrystallization during the drastic deformation. We have also found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 25 publications
3
2
0
Order By: Relevance
“…It is interesting to note that the typical hardness data reported for the base AZ31 Mg alloy is about 0·73–0·78 GPa. 24,25 These data matched favourably with those measured in the present work for the base AZ31 Mg alloy. Further, the nanohardness data measured in the present work matched favourably with those reported for other MAO coatings.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…It is interesting to note that the typical hardness data reported for the base AZ31 Mg alloy is about 0·73–0·78 GPa. 24,25 These data matched favourably with those measured in the present work for the base AZ31 Mg alloy. Further, the nanohardness data measured in the present work matched favourably with those reported for other MAO coatings.…”
Section: Resultssupporting
confidence: 89%
“…26,27 Clearly, depending on the processing technique, the hardness of MgO has been reported to be about five times to an order of magnitude higher than that of the AZ31 Mg alloy. 24,25 These facts 26,27 can certainly rationalise the present data (Fig. 4 c – f ) which showed that the MAO coatings had H and E values as high as about 3–7 times and 1·5–2·5 times those of the as received AZ31 Mg alloy respectively.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…1, the strongest XRD diffraction peak of AZ31B alloy is (0002). This peak is also found the strongest XRD diffraction peak of AZ31 alloy [25]. Fig.…”
Section: Methodsmentioning
confidence: 69%